The correlation between mental health and eating behavior in Indonesian college students: a cross-sectional study - Dewi, Agil Dhiemitra Aulia; Muniandy, Naleena Devi; Subardjo, Ratna Yunita Setiyani; Nurmaguphita, Deasti; Fauzia, Faurina Risca (Universitas 'Aisyiyah Yogyakarta, 2025)
The prevalence of mental health disorders in Indonesia from the 2018 Basic Health Research data shows anxiety disorders of 9.8%, depression of 6%. Whereas, in 2022 from I-NAMHS data, the value increased 26.7% for anxiety disorders and total mental disorders of 34.9%, especially among adolescents and students. This study aims to explore the eating behavior and mental health status of college students in Indonesia. This study employed a quantitative descriptive research design with a cross-sectional approach. The inclusion criteria for this study included college students in Indonesia from diploma/S1/S2 programs aged 16-30 years. The exclusion criteria for the study were research respondents who were diagnosed by a doctor with chronic diseases such as diabetes, kidney failure, heart disease, stroke, mental or psychiatric disorders. Quantitative research data collection used online questionnaires (DASS-21 and EBPQ) which were distributed to respondents using social media platforms. The sample size of the study was 549 people. The sample selection used the Convenience Sampling method. Data were analyzed using STATA. The study showed that 549 respondents from 32 provinces in Indonesia; 68 (12.39%) people experienced depression; 166 (30.24%) people experienced anxiety, and 37 (6.74%) people experienced stress. Stress, anxiety, and depression showed a significant relationship to emotional eating behavior, fast food planning, and skipping meals (p<0.05). This study can provide a deeper understanding of stress, anxiety, and depression that can affect eating behavior, so that it can be the basis for public education and interventions for healthier eating patterns to improve mental and physical health.